2000
DOI: 10.1590/s0100-06832000000300008
|View full text |Cite
|
Sign up to set email alerts
|

Peletização de sementes de sorgo com calcário e com termofosfato e sua influência na absorção de fósforo e de potássio

Abstract: RESUMOO trabalho foi realizado com o objetivo de avaliar a influência da peletização de sementes de três cultivares de sorgo (Sorghum bicolor (L.) Moench), cv. BRS 701, BRS 304 e BRS 601, com calcário e com termofosfato magnesiano, na absorção de P e de K. Sementes peletizadas e não peletizadas foram colocadas para germinar, por oito dias, em temperatura ambiente. Após este período, oito plântulas com crescimento uniforme (parte aérea e raiz) foram distribuídas em vasos que continham solução nutritiva completa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The study verified no differences between conventional and encrusted seeds. However, VASCONCELLOS et al (2000), evaluating the effect of coating in sorghum seeds, verified differences in shoot length in seedlings, and MAGALHÃES et al (1994) showed that seed pelleting influences growth and development of seedling, the magnitude of the effect depending on the cultivars and the kind of coating used.…”
Section: (Usberti and Martins 2007)mentioning
confidence: 99%
“…The study verified no differences between conventional and encrusted seeds. However, VASCONCELLOS et al (2000), evaluating the effect of coating in sorghum seeds, verified differences in shoot length in seedlings, and MAGALHÃES et al (1994) showed that seed pelleting influences growth and development of seedling, the magnitude of the effect depending on the cultivars and the kind of coating used.…”
Section: (Usberti and Martins 2007)mentioning
confidence: 99%